THE INFLUENCE OF UNDERSTANDING Q.S. AL-BAQARAH VERSE 148 ON THE MOTIVATION TO WORSHIP AMONG CLASS XI-D STUDENTS AT MAN 2 SUMEDANG - Simtiyah Nur Aisyah; Dindin Saefudin; Moch. Ichsan Zaelani (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
The main problem in this research is how the understanding of Q.S. Al-Baqarah verse 148 by class XI-D students, the motivation for worship among class XI-D students, and the influence of understanding Q.S. Al-Baqarah verse 148 on the motivation for worship among class XI-D students at MAN 2 Sumedang. This research aims to determine the understanding of Q.S. Al-Baqarah verse 148 by class XI-D students, the motivation for worship among class XI-D students, and the influence of understanding Q.S. Al-Baqarah verse 148 on the motivation for worship among class XI-D students. This study uses a quantitative approach with a correlation method. The research technique used is to distribute questionnaires to respondents. The population in this study consisted of 25 people, making this a population study. Because the sample studied was less than 100 people. The data collection techniques used were observation, documentation, and questionnaires. Based on the results of the test using the SPSS application, the understanding of Q.S. Al-Baqarah verse 148 by class XI-D students is categorized as good with a percentage of 76%. Meanwhile, the motivation for worship among class XI-D students is categorized as very good with a percentage of 89%. The correlation test between variable X (understanding of Q.S. Al-Baqarah verse 148) and variable Y (motivation for worship) yielded a figure of 0.268 or 26.8%. Therefore, the influence between variable X and variable Y is categorized as low. The remaining 73.2% is determined by other factors.